1992
DOI: 10.1159/000261480
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Occlusion on the Fluoride Distribution in Rat Molar Cementum

Abstract: This study was undertaken to examine the influence of occlusion on the fluoride distribution in cementum following an experiment in which the occlusion in rats was locally altered by extracting the upper left molar. These and control rats with normal occlusion were given water containing 0 or 100 ppm fluoride for 12 weeks. The fluoride distributions in cementum from both first lower molars of the same animal were compared. The fluoride concentrations had increased throughout the tissue as a result of increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…We based the H2 prediction on the functional concept described by Hillson [3] that tooth occlusal surfaces can be repositioned by remodelling the periodontal ligament fibres and creation of new fibres that are eventually entrapped by the growing cementum. Experimental support seems inconclusive, in rats, in which an opposing molar was extracted, the growth of cementum of these molars was less than that of the control contralateral molar that their occlusion was not modified [46]. In a similar experiment on rats carried out by Tsuchiya et al [47] M1 was extracted, as a consequence the adjacent M2 and M3 showed a significant distal drift and the proliferation of acellular 5.…”
Section: Plos Onementioning
confidence: 96%
“…We based the H2 prediction on the functional concept described by Hillson [3] that tooth occlusal surfaces can be repositioned by remodelling the periodontal ligament fibres and creation of new fibres that are eventually entrapped by the growing cementum. Experimental support seems inconclusive, in rats, in which an opposing molar was extracted, the growth of cementum of these molars was less than that of the control contralateral molar that their occlusion was not modified [46]. In a similar experiment on rats carried out by Tsuchiya et al [47] M1 was extracted, as a consequence the adjacent M2 and M3 showed a significant distal drift and the proliferation of acellular 5.…”
Section: Plos Onementioning
confidence: 96%